Both psoriasis and benign migratory glossitis are associated with HLA-Cw6 - Gonzaga, H. F.; Torres, E. A.; Alchorne, M. M. A.; Gerbase-Delima, M. (Oxford University Press (OUP), 1996)
This study was undertaken to investigate human leucocyte antigen (HLA) associations with benign migratory glossitis and psoriasis in Brazilian patients and particularly to determine whether benign migratory glossitis is also associated with HLA-Cw6, the classical association observed in psoriasis. The results showed a highly significant association of Cw6 with both psoriasis and benign migratory glossitis, with this antigen being present in 59.% of the patients with psoriasis, in 43.8% of the patients with benign migratory glossitis, and in only 12.6% of the controls. Other significant positive associations, although at a lower significance level, were with B13, both in psoriasis and in benign migratory glossitis, and with B17, only in psoriasis. To our knowledge, this is the first report on the association of Cw6 with benign migratory glossitis. We believe that this finding reinforces the concept of a pathogenetic relationship between benign migratory glossitis and psoriasis.
Keywords: HLA antigen; clinical article; controlled study; female; geographic tongue; human; male; priority journal; psoriasis; Female; Glossitis, Benign Migratory; HLA Antigens; HLA-C Antigens; Humans; Male; Psoriasis